Unveiling bonding states and roles of edges in nitrogen-doped graphene nanoribbon by X-ray photoelectron spectroscopy. (15th November 2021) - Yamada, Yasuhiro; Tanaka, Haruki; Kubo, Shingo; Sato, Satoshi
Abstract: X-ray photoelectron spectroscopy (XPS) is among the most utilized analytical methods for nitrogen-doped carbon materials. Clarifying the assignments of nitrogen-doped carbon materials with different degrees of carbonization, which relates to conjugated systems, is essential to correlate structures with the performance of various applications, but such precise assignments were challenging. In this work, precise analyses were conducted to overcome the difficulty to assign the peaks of carbon materials with different degrees of carbonization, different edges, and various nitrogen-containing functional groups in graphene nanoribbons (GNRs), such as nitrile, pyridinic, primary with/without charges, secondary with/without charge, tertiary without charges (graphitic nitrogen), and quaternary nitrogen. Electrons donated from hydrogen and Madelung potentials showed a higher correlation to the peak shift of C1s and N1s XPS spectra than Mulliken charges on nitrogen. Zigzag edges showed a greater influence on the peak shift of tertiary amine (graphitic nitrogen) than armchair edges on XPS spectra. Besides, as the degree of carbonization is increased from aromatic compound-like structures to GNRs, the peak positions of C–N in C1s and N1s XPS spectra shifted to higher binding energies. This research proved that XPS could be applied to the precise structural analyses of nitrogen-containing carbon materials. Graphical abstract: Image 1